Палеоліт у дослідженнях Д. Я. Телегіна - Степанчук, В.М. (Археологія і давня історія України, 2020)
Статтю присвячено висвітленню маловідомого
аспекту наукової діяльності Д. Я. Телегіна, а саме
його дослідженням, пов’язаним з палеолітичними
пам’ятками і палеолітичною проблематикою.
Хоча цей напрямок вочевидь не був головним в колі
інтересів вченого, але, тим не менш, цікавість до
палеоліту супроводжувала його протягом усього
наукового життя. The article is devoted to the coverage of a littleknown
aspect of D. Ya. Telehin’s scientific activity,
namely his research related to Palaeolithic sites and
Palaeolithic issues. Although this was clearly not the
main area of the scientist’s concern, his interest for
Palaeolithic studies has accompanied him throughout
his scientific life.
In the early 1950s, D. Ya. Telehin participated in the
works of I. F. Levytskyi at the site Mynivskyi Yar at
Seversky Donets, in eastern Ukraine. The lower layer
of the site belongs to the period 18—13 thousand years
ago. In fact, at the time of excavations, it was the only
Upper Palaeolithic site in the region that was investigated
on a relatively large area.
In the mid-twentieth century, a cascade of new hydroelectric
power plants and reservoirs was being built
on the Dnieper. During the field seasons of 1953 and
1957, D. Ya. Telehin’s explorations in the area of construction
of the Kakhovskaya hydroelectric power plant
and the Kakhovskoye reservoir discovered, in addition
to numerous sites from later periods, the first upper
Palaeolithic locations of the Lower Dnieper, namely:
Shyroka, Valivalska and Merzlyakova gullies.
In 1975 together with N. I. Tarasenko, D. Ya. Telegin
conducts excavations at the Rogalyk farm. According
to modern interpretation, the remains of three new
stratified sites were discovered during these works.
The authors have identified the materials as early Mesolithic;
they are now attributed to the final Palaeolithic.
In 1976 D. Ya. Telehin researches the Upper Palaeolithic
site of Zbranky near the eponymous village in
the Ovruch loess area. The materials found once again,
after the works of I. F. Levytskyi and V. A. Mesyats,
confirmed that this region was actively exploited by the
Palaeolithic man at the end of the Pleistocene.
A number of new, mostly surface, Upper Palaeolithic
sites were discovered by the «Dnieper-Donbas»
and «Slavutych» expeditions led by D. Ya. Telehin in
1970—74 and 1980—83 on the territory of the Middle
Dnieper Basin (Chernyavshchyna, Pereschepyno,
Khizhnyakivka, etc.) and the middle reaches of Southern
Buh (Apolyanka, Berezyno).
During the 1980s, D. Ya. Telehin investigated the
area of the left bank of the Dnieper River near the
mouth of the Sula River. This work resulted in the
discovery of a new concentration of Upper Palaeolithic
sites. The features of lithic assemblages make it possible
to identify groups of later and earlier sites in the
preliminary view, including the so-called archaic Upper
Palaeolithic.
In 1984, D. Ya. Telehin investigated the location of
Semenivka 1 in Baryshevsky district of Kiev region
in the valley of Trubizh river. The peculiarities of the
stone tools allowed to see the nearest analogies to the
findings in the materials of the sites of Epigravettian
mammoth hunters. Studies at Semenivka 1 gave an
impulse for further searches in this area.
The brief overview offered shows that although Palaeolithic
studies were not in the focus of D. Ya. Telehin’s
attention, his works are nevertheless deservedly
included in the general fund for achievements in domestic
Palaeolithic studies.